2015
DOI: 10.1371/journal.pgen.1005358
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between Paxillin-like Protein Pxl1 and Glucan Synthase Bgs1 Is Essential for Actomyosin Ring Stability and Septum Formation in Fission Yeast

Abstract: In fungal cells cytokinesis requires coordinated closure of a contractile actomyosin ring (CAR) and synthesis of a special cell wall structure known as the division septum. Many CAR proteins have been identified and characterized, but how these molecules interact with the septum synthesis enzymes to form the septum remains unclear. Our genetic study using fission yeast shows that cooperation between the paxillin homolog Pxl1, required for ring integrity, and Bgs1, the enzyme responsible for linear β(1,3)glucan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
0
12

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(122 citation statements)
references
References 50 publications
(100 reference statements)
8
102
0
12
Order By: Relevance
“…Despite these observations, it is still unknown whether it is Bgs1 itself or its product that is responsible for the stable AMR maintenance in the cell middle and how this attachment is achieved. Recently, it has been reported that absence of paxillin Pxl1, a conserved ring protein that is required for AMR integrity and whose localization depends on the SH3 domain of Cdc15 (89)(90)(91)(92), induces simultaneous Bgs1 sliding and AMR sliding from the cell middle, indicating that the mere presence of Bgs1 alone is not enough to stably maintain the ring location (43). In agreement, the cps1-191 mutant, in which the function of Bgs1 is compromised, also displays AMR sliding (43,46,87,88).…”
Section: Anchorage and Maintenance Of The Amr In The Cell Middle Plasmentioning
confidence: 97%
See 4 more Smart Citations
“…Despite these observations, it is still unknown whether it is Bgs1 itself or its product that is responsible for the stable AMR maintenance in the cell middle and how this attachment is achieved. Recently, it has been reported that absence of paxillin Pxl1, a conserved ring protein that is required for AMR integrity and whose localization depends on the SH3 domain of Cdc15 (89)(90)(91)(92), induces simultaneous Bgs1 sliding and AMR sliding from the cell middle, indicating that the mere presence of Bgs1 alone is not enough to stably maintain the ring location (43). In agreement, the cps1-191 mutant, in which the function of Bgs1 is compromised, also displays AMR sliding (43,46,87,88).…”
Section: Anchorage and Maintenance Of The Amr In The Cell Middle Plasmentioning
confidence: 97%
“…However, since there are no biochemical data supporting the proposed reduction of the septum ␤(1,3)-D-glucan or the in vitro GS activity, it is unknown how these mutations compromise the biosynthetic activity of Bgs1. It has recently been reported that cps1-191 allows the slow formation of a partial septum which is heterogeneously stained with the fluorochrome calcofluor white (CW), so it is possible that this mutated version of Bgs1 still maintains some residual activity at high temperatures (43,71). The finding that Bgs1 was localized at the AMR, and that it was essential for cell survival, suggested that it was required for PS formation (44,45).…”
Section: Synthesis Of the Fission Yeast Septummentioning
confidence: 99%
See 3 more Smart Citations